Reflection on Complexity at the End-of-Life—More Nuanced than Simply Treating Patients the Way We Would Want to be Treated - Neil A. Nijhawan (Palliative Medicine and Hospice Care, 2023)
I relocated to the United Arab Emirates (UAE) just over three years ago, to start a new palliative care service in Abu Dhabi. Palliative care remains a relatively unknown medical specialty here in the UAE both among clinicians and the public.